Factors Affecting Capital Structure of Small-Medium Enterprises Listed in Indonesia Stock Exchange - Uun Fukuludin; Farah Margaretha Leon; Yosephina Endang Purba (Universitas Trisakti, 2021)
This study aims to analyze the factors that influence the capital structure of SMEs, by examining the effect of the independent variables of profitability, growth of opportunity, collateral, corporate tax, tax shield, non-debt tax shield, liquidity, earnings volatility, and cash flow volatility; to the capital structure of SMEs as the dependent variable. As for anticipation of bias, the study uses size, company age, GDP, interest rates, inflation, and market capitalization as control variables. The data used in this study is a combination of cross-sectional and time-series, which is called panel data. The number of samples in this study was 53 SMEs listed on the Indonesia Stock Exchange during 2016-2020. The result of this study shows that profitability has a significant negative effect on DAR, but has no effect on DER. Growth of total assets has no effect on DAR and DER, growth of tangible assets has no effect on DAR and DER, and growth of market value has a significant positive effect on DAR, but has no effect on DER. Collateral harms DAR and DER. Corporate tax does not affect DAR but has a significant negative effect on DER. Tax shield has a significant negative effect on DAR and DER. Non-debt tax shield does not affect DAR but has a significant negative effect on DER. Liquidity has a significant negative effect on DAR and DER. Earnings volatility has a significant positive effect on DAR and DER. Cash flow volatility does not affect DAR and DER. Company size has a significant positive effect on DAR and DER. Company age has a significant positive effect on DAR but has a significant negative effect on DER, gross domestic product (GDP) has a significant positive effect on DAR and DER, loan interest rates do not affect DAR, but harm DER. Inflation has no effect on DAR but harms DER, and market capitalization has a significant negative effect on DAR and DER. This study implies that for investors, it is necessary to conduct a thorough assessment of financial performance and the factors that influence the capital structure before deciding to invest. A high capital structure can reduce potential profits and increase the risk of default. Thus, investors need to pay attention to the factors that have a negative and significant effect with a large level of influence on the capital structure, because if these factors increase, the capital structure will decrease. This will create efficient and effective use of capital and avoid the high cost of equity or cost of debt so that it can be utilized optimally to provide maximum benefits for SMEs and investors